Pengaruh Kemasan, Label Halal, Label Izin P-IRT Terhadap Keputusan Pembelian Konsumen UMKM Kerupuk Ikan - Rifqi Suprapto; Zaky Wahyuddin Azizi (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2020)
The role of SMEs (Small Medium Enterprise) in the economic development of a region is very important, as is the case with Rembang Regency. The purpose of this study is to determine the factors that influence consumer decisions in making purchases so that business people can find out the factors that play an important role in achieving customer satisfaction. Therefore, researchers see the most important thing in a product that will be perceived first by consumers, namely or packaging, halal label and P-IRT label from the Health Office. This type of research used in this research is quantitative research with this research approach is explanatory research. This research was conducted in June-August 2019 to consumers of fish crackers in Rembang Regency. Data collection techniques in this study using a questionnaire. Questionnaire Data analysis techniques in this study used multiple linear regression analysis. The results of the analysis in this study concluded that the product packaging is very influential on the purchasing decision of consumers of fish crackers in Rembang Regency. Packaging attributes such as packaging shape, type of size, the color of packaging, packaging motif and logo packaging are able to convince consumers to buy fish crackers. In contrast to the halal label attribute and permit label from the Dinkes P-IRT which does not have an effect on the fish cracker purchasing decision.